Hybrid Plasmonic Cavity Modes in Arrays of Gold Nanotubes. Issue 4 (25th November 2016) - Wang, Junfeng; Zhang, Cheng; Zhang, Junxi; Song, Haojie; Wang, Pei; Lu, Yonghua; Fei, Guangtao; Xu, Wen; Xu, Wei; Zhang, Lide; Kivshar, Yuri S.; Zhang, Lin
Abstract : Plasmonic structures are known to confine light at the nanometer scale, and they exhibit enhanced electromagnetic fields localized in small mode volumes. Here, plasmonic resonators based on a metamaterial consisting of periodic arrays of gold nanotubes embedded into anodic aluminum oxide are studied and strong confinement of local fields with low losses is demonstrated. Higher‐order resonance modes of surface plasmons localized in gold nanotubes when the nanotube length exceeds some critical values are observed. The numerical simulations suggest that, the electric fields associated with some higher‐order longitudinal modes for the long nanotubes and some lower‐order longitudinal modes for the short nanotubes or the nanotubes with thin walls, are mainly localized at the interfaces between aluminum oxide and gold in the form of the standing‐wave longitudinal plasmonic modes, partially localized in the pores and at two ends of the nanotubes owing to the strong coupling of the Fabry–Pérot resonances with extraordinary optical transmission effect in the periodical structures through the inner nanochannels of the nanotubes, so that the nanotubes play a role of efficient cavity resonators. The existence of hybrid plasmonic resonant cavity modes with asymmetrical distributions of the electric field resulting from the near‐field coupling of both transversal and longitudinal modes in the gold nanotube metamaterials is revealed. Abstract : Gold nanotube arrays for efficient plasmonic cavity resonators are successfully synthesized with a template‐based method. Odd and even harmonics with standing‐wave modes are tuned by nanotube length. Transversal–longitudinal hybrid cavity modes dependent on wall‐thickness and length of nanotubes, perform strong confinements of electric fields localized in pores and at two ends based on extraordinary optical transmission effect through inner nanochannels.